Integrating Digital Technologies Into The Distance Learning Process - Farkhod S. Turabekov, DSc (Genius Journals, 2025)
The article indicates the number of technologies used for teaching in the field of education.
Keywords: Distance learning; distance learning laboratory; aurdino laboratory